2006
DOI: 10.1093/toxsci/kfl033
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Exposure to 2-Aminoanthracene Induces Morphological and Immunocytochemical Changes in Pancreatic Tissues of Fisher-344 Rats

Abstract: Toxic chemicals ingested as the result of environmental exposures or other risk factors such as cigarette smoking may increase the risk of developing cancer and other diseases such as diabetes. 2-Aminoanthracene (2-AA) was investigated to determine toxic effects of chronic dietary exposure upon major organ systems including the pancreas. Fisher-344 rats were fed 2-AA (50-100 mg/kg of diet) and euthanized at 14, 30, 63, and 80 days. Growth, tissue histological, immunocytochemical, and clinical pathological end … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 45 publications
1
14
0
1
Order By: Relevance
“…Analysis of histological, immunocytochemical, and clinical pathological end points showed changes in the endocrine and exocrine pancreas cellular morphology (Boudreau et al, 2006). Similar investigations found pancreatic differentially expressed genes that were involved in energy metabolism in the pancreas, and protein digestion.…”
Section: Introductionmentioning
confidence: 61%
See 2 more Smart Citations
“…Analysis of histological, immunocytochemical, and clinical pathological end points showed changes in the endocrine and exocrine pancreas cellular morphology (Boudreau et al, 2006). Similar investigations found pancreatic differentially expressed genes that were involved in energy metabolism in the pancreas, and protein digestion.…”
Section: Introductionmentioning
confidence: 61%
“…They are employed in the manufacture of dyes, drugs, inks, rubber antioxi-dants, plastics, and agricultural chemicals. These aromatic amines are also used as curing agents in synthesizing epoxy resins and polyurethanes and are found in road tars and synthetic fuels (Boudreau et al, 2006;Snyderwine et al, 1992;Zhu et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Others have observed that environmental exposures in childhood seem to trigger chronic diseases that affect adults [111213]. Insulin-dependent diabetes mellitus, which results from specific disruption of the pancreatic islet insulin-secreting β-cells, is induced in experimental animals by toxic agents, including chemicals that are byproducts of cigarette smoking [1415]. …”
Section: Introductionmentioning
confidence: 99%
“…Fluorophore 1-aminoanthracene (1-AMA) is widely used to study interaction between lipocalin family proteins and their ligands [6][7][8][9][10][11][12]. Aminoanthracene is known to be a cytotoxic compound [13] inducing DNA damaging and thus altering proteins structures.…”
Section: Introductionmentioning
confidence: 99%